THE RELATIONSHIP BETWEEN DIET AND ACNE VULGARIS IN STUDENTS OF FACULTY OF MEDICINE 2022-2023 PRIMA INDONESIA UNIVERSITY : DIET AND ACNE VULGARIS - Valensia, Valensia; Oentari, Widyaningsih; Chandra, Rudi (STIKes Mandala Waluya Kendari, 2024)
Background: The skin is the outermost part of the body that functions as a barrier between humans and the environment. The structure of the skin is affected by various factors such as climate, age, gender, race, and location in the body. The skin consists of 3 main layers, namely the epidermis, dermis, and subcutaneous. In addition, the skin has sebaceous glands or oil glands located on the skin, hair, and nails. These glands function to maintain skin moisture, especially when they are active and developing during puberty. However, activity can also cause skin problems, such as warts, dermatitis, and acne vulgaris. Methods: The type of research conducted is observational analytical research on the Kendall's Tau design approach. The sampling technique is stratified random sampling. As many as 98 respondents were obtained who met the inclusion criteria of the research object. Results: Shows that the most commonly found sex is female. This study shows that there is no relationship between milk consumption and acne vulgaris. Conclusion: Based on the results of the study, there was no significant relationship between the frequency of milk consumption and acne vulgaris, the amount of milk consumption per day and per week, because milk contains zinc and vitamin A. Zinc functions as an anti-inflammatory agent in acne by inhibiting the growth of C. acnes bacteria, and milk contains vitamin D, so it has a pleiotropic effect that can prevent lesions in acne vulgaris.